Tìm x
I 7-x I + I 4x+1 I = 2x+5
I 2x-7 I - I 5-4x I = -10
Tìm x
I 7-x I + I 4x+1 I
I 2x-7 I - I 5-4x I
tim x biet :
a) ( 2x^2+4 ) - (x^2-3/2 ) = (-3+4x^2)+ ( -4x^2/3+1)
b) ( I xI -4) - ( 2- I-xI ) = 1/3 . I xI -5
tim x biet :
a) ( 2x2+4 ) - (x2-3/2 ) = (-3+4x2)+ ( -4x2/3+1)
b) ( I xI -4) - ( 2- I-xI ) = 1/3 . I xI -5
Không có ngiệm nguyên hay hữu tỉ mà bạn
tim x biet :
a) ( 2x2+4 ) - (x2-3/2 ) = (-3+4x2)+ ( -4x2/3+1)
b) ( I xI -4) - ( 2- I-xI ) = 1/3 . I xI -5
I 7+5x I = 1-4x
I 4x^2 - 2x I + 1 = 2x
I x^2 - 5x + 4 I = x+4
I 4 - 3x I = 3x -4
I 1+5x I = 1 + 5x
I x^2 - 3x + 1 I = 2x-3
I x-1 I = x^2 -x
|7 + 5x| = 1 - 4x
=> \(\orbr{\begin{cases}7+5x=1-4x\left(đk:x\le\frac{1}{4}\right)\\7+5x=4x-1\left(đk:x\ge\frac{1}{4}\right)\end{cases}}\)
=> \(\orbr{\begin{cases}7-1=-4x-5x\\7+1=4x-5x\end{cases}}\)
=> \(\orbr{\begin{cases}6=-9x\\8=-x\end{cases}}\)
=> \(\orbr{\begin{cases}x=-\frac{2}{3}\left(tm\right)\\x=-8\left(ktm\right)\end{cases}}\)
|4x2 - 2x| + 1 = 2x
=> |4x2 - 2x| = 2x - 1
=> \(\orbr{\begin{cases}4x^2-2x=2x-1\left(đk:x\ge\frac{1}{2}\right)\\4x^2-2x=1-2x\left(đk:x\le\frac{1}{2}\right)\end{cases}}\)
=> \(\orbr{\begin{cases}4x^2-2x-2x+1=0\\4x^2-2x-1+2x=0\end{cases}}\)
=> \(\orbr{\begin{cases}\left(2x-1\right)^2=0\\4x^2-1=0\end{cases}}\)
=> \(\orbr{\begin{cases}2x-1=0\\x^2=\frac{1}{4}\end{cases}}\)
=> \(\orbr{\begin{cases}x=\frac{1}{2}\\x=\pm\frac{1}{2}\end{cases}}\)(tm)
Vậy ...